An Intermediary Role of Adenine Nucleotides on Free Fatty Acids-Induced Hyperglycemia in Obese Mice - Yang, Xiao; Zhao, Yang; Sun, Qi; Yang, Yunxia; Gao, Yan; Ge, Wenhao; Liu, Junhao; Xu, Xi; Zhang, Jianfa (Frontiers in Endocrinology, 2019)
Increased plasma free fatty acids (FFA) level plays a central role in the development of type 2 diabetes. Our previous studies have shown that plasma 5'-adenosine monophosphate (5’-AMP) elevates and acts as a potential upstream regulator of hyperglycemia in diabetic db/db mice. The relationship between FFA and plasma adenosine nucleotides in type 2 diabetes remains unclear. Here we found that plasma 5’-AMP level was also increased in diabetic mice induced by a high-fat diet and streptozotocin (HFD-STZ), as observed in diabetic db/db mice. The metabolites of adenosine nucleotides in plasma were increased in obese mice compared to lean mice. An acute oil gavage to lean mice increased both FFA and plasma purine metabolites, accompanying with glucose intolerance. 5’-AMP administration resulted in an increase in dose-dependent purine metabolites and different levels of glucose intolerance. FFA induced a release of adenine nucleotides from cultural human umbilical vein endothelial cells (HUVECs) prior to induction of their apoptosis. FFA also reduced red blood cells (RBCs) resistance to reactive oxygen species (ROS), leading to hemolysis, thereby increasing plasma nucleotides. Our results suggest that plasma adenine nucleotides play an intermediary role in FFA-induced glucose intolerance and hyperglycemia in obese mice.